Analisis kriteria penyahsenaraian sekuriti patuh syariah Bursa Malaysia 2020-2021 - Fidlizan Muhammad; Azila Abdul Razak; Mohd Yahya Mohd Hussin; Ahmad Zakirullah Mohamed Shaarani; Salwa Amirah Awang (USIM PRESS, 2024)
Vol. 19, No. 2 Page (58-71)